Control of tetragonality via dehydroxylation of BaTiO3 ultrafine powders. Issue 18 (15th December 2017) - Huang, Y.A.; Lu, B.; Li, D.D.; Tang, Z.H.; Yao, Y.B.; Tao, T.; Liang, B.; Lu, S.G.
Abstract: Nanosized barium titanate (BaTiO3 (BTO)) powders with a pure perovskite phase and high c/a ratio were prepared using a two-step hydrothermal approach followed by removal of hydroxyl groups using organic solvents. No trace of carbonate was observed during the preparation process. The tetragonality of the BTO powder increased with an increase in the hydrothermal process duration on treating the powder at 240 °C with the two-step and one-step processes. The tetragonality increased with a decrease in the hydroxyl group content. The advantages of the two-step process can be ascribed to the two-step nucleation and growth process, and in the second step, BTO particles nucleate directly on the BTO crystallites, resulting in a higher crystallinity and tetragonality (c/a ratio). The new method has the potential to be scaled up for mass production of high-quality BTO nanopowder samples suitable for capacitor and sensor applications.